Νησιά και κεντρική εξουσία κατά τα έτη 1081-1204. Μία παραδοσιακή σχέση σε κρίση; - ΚΩΣΤΟΥΡΑΚΗΣ, Νικόλαος Λεωνίδα (Byzantina Symmeikta, 2020)
During the twelfth century (1081-1204) the Byzantine Empire faced a series of separatist movements, such as those of Theodore Mangaphas in Asia Minor and of Leo Sgouros in southern Greece. The byzantine islands were no exception to the rule, as Crete, Cyprus, Negroponte and Rhodes seem to have pursued their independence from the central government. The aim of this article is to ascertain which of those revolts actually took place, and then to shed light on their character. Researchers have not drawn a definite conclusion concerning the incentives behind the secessionist movements. Some support that the isles were oppressed by the burdens the government imposed, especially taxation, while others have argued that the islands did not manifest any tangible intention to secede. This paper favours the latter view, claiming that ambitious local magnates sought to take advantage of political instability in order to subdue the islands to their personal authority. However, an effort has been made not to overlook the cases where popular discontent fuelled the reaction against imperial authority.